The effect of maternal exercise on maternal and foetal health in obese pregnant women - Šćepanović, Darija (Zdravniški vestnik, 2020)
Background: Obesity during pregnancy represents a global problem and is a major risk factor for complications during pregnancy and labour. Emerging evidence suggests that physical activity during pregnancy might be beneficial for both maternal and foetal health without side effects. The purpose of this systematic review was to review trials evaluating the effect of physical activity on maternal and foetal health in obese pregnant women. Methods: PRISMA guidelines were followed. We searched for randomized controlled trials published until June 2018 on the PubMed, PEDro and CENTRAL databases. We included articles that had a well described physical activity intervention and studied obese pregnant women with BMI>30kg/m2. Results: Ten articles were included in the review. All articles included a physical activity intervention, seven articles included also a dietary intervention. Four articles included a pedometer-based intervention, six articles opted for a supervised physical activity intervention. Physical activity with or without dietary intervention had no effect on lowering the risk for gestational diabetes mellitus or improving neonatal or other maternal outcomes. There were mixed results in gestational weight gain and mode of delivery. Conclusion: We can conclude that physical activity during pregnancy has mixed results on maternal and foetal health in obese pregnant women. There is no evidence from randomized controlled trials that PA during pregnancy in obese women improves maternal or neonatal outcomes, and therefore no clear statements on beneficial effects of PA in this population can currently be made.
Keywords: debelost; exercise; nosečnice; obesity; pregnant women; telesna dejavnost